2020
DOI: 10.1002/dneu.22796
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Hippo signaling: From development to diseases

Abstract: Hippo signaling pathway is a highly conserved and familiar tissue growth regulator, primarily dealing with cell survival, cell proliferation, and apoptosis. The Yes‐associated protein (YAP) is the key transcriptional effector molecule, which is under negative regulation of the Hippo pathway. Wealth of studies have identified crucial roles of Hippo/YAP signaling pathway during the process of development, including the development of neuronal system. We provide here, an overview of the contributions of this sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 121 publications
1
28
0
Order By: Relevance
“…Similarly, the Hippo Signaling pathway was significantly enriched in cLBP and PFC groups. This pathway plays a crucial role in neurodegenerative diseases and neuronal function by regulating neuronal growth and proliferation, differentiation, synaptogenesis, and apoptosis [ 57 , 58 ]. In animal models, Li and colleagues found that the expression of Hippo signaling pathway components (Yap and TAZ) play an essential role in neuropathic pain by regulating synaptic and structural plasticity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Hippo Signaling pathway was significantly enriched in cLBP and PFC groups. This pathway plays a crucial role in neurodegenerative diseases and neuronal function by regulating neuronal growth and proliferation, differentiation, synaptogenesis, and apoptosis [ 57 , 58 ]. In animal models, Li and colleagues found that the expression of Hippo signaling pathway components (Yap and TAZ) play an essential role in neuropathic pain by regulating synaptic and structural plasticity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…TANC2 is highly expressed during brain development and interacts with proteins from important developmental signalling pathways such as Wnt (PRICKLE1/2) and Hippo (ZYX, YWHAB, LATS2), as well as with proteins involved in cilium assembly (CBY1, CEP120) and trafficking (INPP5E) ( Gasparini et al, 2017 ). Both Wnt and Hippo pathway proteins can regulate, among other neurodevelopmental processes, dendritic arborisation and synapse formation ( Budnik and Salinas, 2011 ; Sahu and Mondal, 2021 ). Thus, TANC2 can influence synaptic function through interaction with these pathways leading to NDDs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NPCs differentiation is also induced by FAT4‐DACHS, which further inhibit YAP/TAZ activity 31 . The inhibition of YAP/TAZ by Hippo has been shown to promote neuritogenesis, the sprouting of neurites from neurons, prior to establishment of functional interneural synapses 37 . YAP/TAZ also participate in the programming of neural cell apoptosis.…”
Section: Physiological Functions Of Yap/tazmentioning
confidence: 99%
“…YAP/TAZ also participate in the programming of neural cell apoptosis. Under stressful conditions, the Hippo pathway becomes overactivated, 37 leading to the retainment of YAP in the cytoplasm by interacting with 14‐3‐3 or p73 in the nucleus and induction of apoptosis 38,39 …”
Section: Physiological Functions Of Yap/tazmentioning
confidence: 99%